2019
DOI: 10.7150/ijms.32795
|View full text |Cite
|
Sign up to set email alerts
|

Superinfection of hepatitis A virus in hepatocytes infected with hepatitis B virus

Abstract: Hepatitis A virus (HAV) infection is a major cause of acute hepatitis including acute liver failure. Hepatitis B infection (HBV) occurs worldwide, with the highest rates in Asian and African countries, and there are several reports that HAV infection may have a more severe clinical course in patients with chronic HBV infection. We previously demonstrated that Japanese miso extracts have inhibitory effects on HAV replication. In the present study, we examined the replication of HAV and HBV in a hepatocyte super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Moreover, evidence suggests that HAV internal ribosomal entry-site (IRES) is an attractive target of antiviral agents against HAV and the JAK2 inhibitor AZD1480 can inhibit IRES activity and HAV replication [75,76]. Recently, Japanese miso extracts have been reported to have inhibitory effects on HAV replication not only in patients infected with HAV but also in patients superinfected with HAV and HBV [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, evidence suggests that HAV internal ribosomal entry-site (IRES) is an attractive target of antiviral agents against HAV and the JAK2 inhibitor AZD1480 can inhibit IRES activity and HAV replication [75,76]. Recently, Japanese miso extracts have been reported to have inhibitory effects on HAV replication not only in patients infected with HAV but also in patients superinfected with HAV and HBV [9].…”
Section: Discussionmentioning
confidence: 99%
“…HAV infection is the second largest cause of fulminant viral hepatitis characterized by massive hepatocyte necrosis and inflammatory infiltrate after hepatitis B virus (HBV) infection [ 8 ]. In addition, superinfection of HAV with HBV is also a health problem in regions with high endemicity levels both of HAV and HBV [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that the HAV replication is similar between HepG2.2.15 and HepG2, 96 h after HAV infection. However, HBV replication is inhibited in HAV-infected HepG2.2.15, compared to HepG2.2.15 without HAV infection [ 73 ].…”
Section: Coinfection Of Hav With Hbvmentioning
confidence: 99%
“…We also observed that the replication of both HAV and HBV is suppressed in human hepatocyte PXB cells superinfected with HAV and HBV, compared to those mono-infected with HAV or HBV [ 73 ]. Thus, HAV infection seems to inhibit HBV replication.…”
Section: Coinfection Of Hav With Hbvmentioning
confidence: 99%
See 1 more Smart Citation